Pelvic floor muscle dysfunction at 3D transperineal ultrasound in maternal exposure to gestational diabetes mellitus: A prospective cohort study during pregnancy - Pinheiro, Fabiane A. [UNESP]; Sartorão Filho, Carlos I. [UNESP]; Prudencio, Caroline B. [UNESP]; Nunes, Sthefanie K. [UNESP]; Pascon, Tawana [UNESP]; Hallur, Ragavendra L. S. [UNESP]; Takano, Luis [UNESP]; Enriquez, Eusébio M. A. [UNESP]; Catinelli, Bruna B. [UNESP]; Carr, Aline M. [UNESP]; Junginger, Baerbel; Rudge, Marilza V. C. [UNESP]; et al. (Wiley, 2022)
Aim: This study aimed to assess, for the first time, the dynamic morphometry of pelvic floor muscles (PFM) using three-dimensional transperineal ultrasound (3D-TPUS) and its progression at two-time points of gestation between women with and without gestational diabetes mellitus (GDM), and whether the PFM dysfunction is connected to GDM. Methods: The study comprised 83 consecutive pregnant women with (n = 38) and without (n = 45) GDM screened at 24–30 and 38–40 weeks of gestation. 3D-TPUS and a mobility test were used to quantify PFM dynamic morphometry during maximum contraction and the Valsalva maneuver. Results: When compared to the control group, GDM women had no significant variations in all levator hiatal dimensions at 24–30 weeks of gestation. Meanwhile, women with GDM experienced an increase in levator hiatal area (LHa) (p < 0.000) during PFM contraction and enlargement in LHa (p < 0.001) during Valsalva maneuver (p = 0.010) at 38–40 weeks of gestation. As a result, the mobility index among GDM women had a lower value (p = 0.000). The dynamic morphometry development of PFM in GDM women at two stages during pregnancy revealed a substantial decrease (p = 0.000) in all LHa dimensions of contraction, distension, and mobility. Conclusions: Using 3D-TPUS, we found that GDM women had a specific pattern of PFM functional changes in the third trimester of pregnancy. These initial findings revealed alterations in PFM functionality, such as decreased contractility, distensibility, or mobility. This dysfunctional PFM could contribute to the long-term development of pelvic floor dysfunction years after a GDM pregnancy.
Keywords: 3D transperineal ultrasound; gestational diabetes mellitus; muscle contraction; pelvic floor muscle; pregnancy; valsalva maneuver